Virtual try-on using generative-AI - Teo, Zi Ning (2024)
In today’s rapidly changing world, technology and fashion have come together in exciting new ways. One of the most innovative developments is virtual try-on applications. These apps let users try on clothes digitally without needing to go to physical stores. This has become especially popular during the COVID-19 pandemic, as it provides a safe and easy way for people to shop for clothes from the comfort of their homes. Instead of going to a store to see how an outfit looks, users can simply upload a picture of themselves or use their camera to see what the clothes would look like on them in real time.One of the key reasons why these apps are becoming so popular is the use of advanced technology, particularly generative artificial intelligence (AI). For example, some virtual try-on applications use image-based virtual try-ons that are powered by generative adversarial networks (GANs). These networks help create realistic images that show how clothes would look on a person. In addition, augmented reality (AR) and virtual reality (VR) are being used to make the virtual try-on experience even more interactive. This project will focus on developing a seamless and intuitive virtual try-on experience that appeals to modern consumers. With the power of AI and virtual reality, users will be able to try on clothes, experiment with new styles, and make purchasing decisions in a way that’s convenient, fun, and perfectly suited for the digital age.